PERBANDINGAN HASIL BELAJAR SOSIOLOGI BAGI SISWA BERKESULITAN BELAJAR MELALUI MODEL ARTIKULASI DAN MIND MAPPING - Wahyuning Yantini; Sudjarwo Sudjarwo; Pargito Pargito (Faculty of Teacher Training and Education, University of Lampung, 2013)
This study was conducted because of the group of students who deliberately violate school rules with any activity that does not comply with the regulations that apply in school, such as truant during the learning process, interfere with teaching and learning activities/making noise in class, do not do chores/work home, late for school, and smoking in the school environment, so it is classified as a troubled student. The results showed: (1) there is a difference in student learning outcomes sociology that learning disabilities between the model of learning and mind mapping and articulation between initial ability level of high, medium and low together; (2) there is difference in outcomes between students who study sociology learning disabilities through the articulation of learning models and learning models on the students' mind mapping, (3) there are differences in learning outcomes between students who sociology learning disabilities with the ability level initially high, medium and low, (4) there is no significant interaction between learning model with initial ability level of students, and (5) methods of mind mapping more effectively used in carrying out the process of learning rather than learning model articulation sociology.Kata kunci: kesulitan belajar, model artikulasi, model pembelajaran, mind mapping